Analysis of Accounting Learning Difficulties in MYOB Accounting - Asmawan, Moh. Chairil; Rismawati, Rina (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine 1) Types of student difficulties in learning MYOB Accounting at SMK 3 Muhammadiyah Gemolong, 2) Factors causing student learning difficulties in learning MYOB Accounting at SMK 3 Muhammadiyah Gemolong, 3) Teacher strategies in overcoming student difficulties in learning MYOB Accounting at SMK 3 Muhammadiyah Gemolong. This study uses a qualitative research design with a case study approach. Data collection techniques used are interviews, observation and documentation. To analyze and check the validity of the data using data triangulation techniques. The stages of data analysis include reducing data, displaying data, and drawing conclusions. The results of this study indicate that: (1) The types of student difficulties in learning MYOB Accounting are categorized as quite severe, namely in classifying transactions and entering data and a lack of understanding of the language in the MYOB application (2) There are several factors that cause learning difficulties including internal factors, namely lack of ability students analyze and enter transaction data and understanding of language in the MYOB application, Lack of student readiness in the completeness of MYOB notebooks and study guidebooks. Lack of interest in students participating in MYOB learning because the material is difficult to understand and external factors, namely not having a laptop / personal computer at home and the way the teacher teaches which lacks a variety of learning methods that hinders MYOB Accounting (3) Several learning strategies are carried out by the teacher to overcome difficulties students in learning, namely by applying various learning methods, further improving personal approaches with students, and evaluating learning.